Model Regresi Hazard Rate Weibull Kesembuhan Pasien Rawat Inap Demam Berdarah Dengue (DBD) Di RSUD Panglima Sebaya Tanah Grogot - Fajriati, Nur Ainun; Suyitno, Suyitno; Wasono, Wasono (Program Studi Statistika FMIPA Universitas Mulawarman, 2022)
Univariate Weibull Regression (RWU) is a regression model development of the Univariate Weibull distribution, where the scale parameters is expressed in terms of the regression parameters. Univariate Weibull Regression Models discussed in this study are Weibull survival regression and the Weibull hazard regression model. Weibull regression models in this study was applied to lifetime data containing the right censored data for Dengue Hemorrhagic Fever (DHF) inpatients at the Regional General Hospital (RSUD) Panglima Sebaya Tanah Grogot, Paser Regency, Kalimatan Tinur. The purpose of this study was to obtain a Weibull regression model and to determine the factors that affect the patients is survive (have not recovery) and the recovery rate of DHF patients. The parameter estimation is the Maximum Likelihood Estimation (MLE) which is solved by using the Newton-Raphson iterative method. The study conclude that the factors influencing the patients is survive (have not recovery) and the recovery rate of DHF patients at RSUD Panglima Sebaya Tanah Grogot were platelets and leucocytes.